Assessment Performance at Al- Thawra Signalized Intersection in Babil City - Mahdi, Ali Salah; Ahmad, Nahla (Anbar Journal of Engineering Sciences, 2022)
Hilla cities center of province Babil is one of the most important cities in Iraq 100 km (62 mi) south of Baghdad .its relate  the Governorate Baghdad with Governorates south                                            Al-Thawra signalized intersection is one of the most important intersections   in AL-Hilla city Being a major crossing point to the governorates of holy Karbala and Baghdad.The excessive traffic volumes, during the peak periods (at morning and evening), of vehicles that entering the intersection increase traffic density, reduce travel speed, increase travel time, and increase the delay values This paper aims to assess the traffic performance of Al-thawra signalized intersection in Babil city that is consistent with the existing conditions and intersection's geometric properties. For all approaches, video recording has been used to collect traffic volume data. These data are taken out of videos from Babil police cameras (department of communications and information systems)..The intersection was evaluated and analyzed using the SYNCHRO 10.0 software, and the best option was selected. The outcome of the evaluation process indicated that the intersection is operated at the level of service (LOS F) and with a control delay of 162.5 seconds.by recommending a variety of strategies, ranging from signal optimization to geometric enhancements. The suggestion of widening the pavement in the north-south direction was found to be the best solution.  resulting in a decrease in vehicle delays from 162.2 seconds to 95.4 seconds  and the level of service remains constant  (LOS F)  considered an acceptable and cost-effective solution to the intersection's problems.